Morphology and photodegradation performance of Ag3PO4 prepared by (NH4)3PO4, (NH4)2HPO4 and NH4H2PO4. Issue 5 (1st April 2017) - Song, Xianghua; Li, Ruiping; Xiang, Miaomiao; Hong, Shaoming; Yao, Kun; Huang, Yingping
Abstract: Ag3 PO4 was prepared by a facile precipitation process using three types of phosphate salts ((NH4 )3 PO4, (NH4 )2 HPO4, and NH4 H2 PO4 ) as a precipitant. The XRD, SEM and XPS results revealed that the pH of phosphate salt effectively controlled the shape and size of as-prepared Ag3 PO4 samples through affecting the existing species and release rate of PO4 3- ions in solution. The cauliflower-like spheres Ag3 PO4 synthesized by (NH4 )3 PO4 exhibited best photocatalytic activity towards Congo red degradation under visible light irradiation, as was primarily attributed to its smaller size and less OH-related defects compared with Ag3 PO4 prepared from (NH4 )2 HPO4, and NH4 H2 PO4 . In addition, this Ag3 PO4 photocatalyst could degrade Rhodamine B, Malachite Green and Methylene blue, but was not much active for the degradation of Surpho Rhodamine B. More importantly, the dye decolorization efficiency was poorly correlated with the dye mineralization efficiency, which was evidenced by the removal of total organic carbon. The recyclability and stability of the photocatalysts were also evaluated by cycle test experiments using Ag3 PO4 prepared by (NH4 )3 PO4 .